Acoustic mist ionization mass spectrometry (AMI-MS) as a drug discovery platform. (3rd July 2019) - Sinclair, Ian; Davies, Gareth; Semple, Hannah
ABSTRACT: Introduction: The expansion of label free mass spectrometry into early drug discovery was always predicted to provide improvements in data quality and depth with the potential to reduce costs but has previously been limited by throughput. There are several techniques that vary by sample introduction technology or ionization technique that try to address the challenges in this area. Areas covered: In this review, the authors describe the deployment of such a device, combining acoustic mist ionization and time-of-flight mass spectrometry. The potential impact of this instrument is discussed with case studies reporting screening across a series of enzyme target classes and chemical triage assays which have generated early chemical equity for drug projects. Expert opinion: In our expert opinion, we look forward to the large-scale adoption of mass spectrometry as a high throughput screening approach. The expansion of applications enabled by these technologies such as triage assays and metabolic profiling will also be explored.